Effectiveness and safety of tofacitinib for ulcerative colitis: two‐year results of the ICC Registry. Issue 1 (25th October 2022) - Straatmijer, Tessa; van Schaik, Fiona D. M.; Bodelier, Alexander G. L.; Visschedijk, Marijn; de Vries, Annemarie C.; Ponsioen, Cyriel Y.; Pierik, Marieke; van Bodegraven, Ad A.; West, Rachel L.; de Boer, Nanne K. H.; Srivastava, Nidhi; Romkens, Tessa E. H.; et al.
Summary: Background: Tofacitinib is an oral Janus kinase (JAK) inhibitor and is registered for the treatment of ulcerative colitis (UC). The effectiveness of tofacitinib has been evaluated up to 12 months of treatment. Aim: The aim of this study was to assess the effectiveness and safety of 24 months of tofacitinib use in UC patients in the Netherlands. Methods: Patients initiating tofacitinib treatment were included in the ICC Registry, a nationwide, observational registry. Patients were prospectively evaluated for up to 24 months. The primary outcome was corticosteroid‐free clinical remission (CSFR, Simple Clinical Colitis Activity Index [SCCAI] ≤2) at week 104. Secondary outcomes included biochemical remission (C‐reactive protein (CRP) ≤5 mg/L and faecal calprotectin (FC) ≤250 μg/g), safety, and discontinuation rate. Results: We included 110 patients of whom 104 (94.5%) were anti‐TNF experienced. After 104 weeks of tofacitinib, 31.8% (34/107) were in CSFR, 23.4% (25/107) in biochemical remission and 18.7% (20/107) in combined clinical and biochemical remission. Of the patients in CSFR at week 52, 76.5% (26/34) remained so after 104 weeks of treatment. Sixty‐one patients (55.5%) discontinued tofacitinib after a median duration of 13 weeks (IQR 7–34). The main reasons for discontinuation were non‐response (59%), loss of response (14.8%), and adverse events (18%). There were 33.9 possible tofacitinib‐related adverse events per 100 patient‐years during follow‐up. Adverse events most probably related to tofacitinib were skin reactions and headaches. There were 6.4 herpes zoster infections per 100 patient‐years. Conclusion: Tofacitinib was effective in 31.8% of patients after 24 months of treatment. Abstract : Effectiveness and safety of tofacitinib for ulcerative colitis: Two‐year results of the ICC Registry